Escaping Materials from Lower Order Thinking Skills in Geschool - Luli Sari Yustina; Besral Besral; Hasnawati Hasnawati (Institut Agama Islam Negeri Imam Bonjol Padang, 2023)
The objective of this study was to determine the distribution of Higher-Order Thinking Skills (HOTS) of EFL materials posted in Geschool. The analysis was made in accordance with the revised Bloom's taxonomy including cognitive and knowledge dimension. Data of this study were collected by using document analysis method which were taken from EFL online materials and tasks in Geschool for grade IX at Junior High School Adabiah Padang. The Geschool online materials were analyzed by using cognitive and knowledge dimension analysis guide. The findings showed that all topics in knowledge dimensions belonged to Lower Order Thinking Skill. Â Meanwhile, in cognitive domain. there were only 14.14% tasks belonged to higher-lorder thinking skill. In the knowledge dimension aspect, most HOTS materials belonged to factual knowledge. While in cognitive aspect, most HOTS questions belonged to remembering level. Â It can be concluded that the majority of EFL materials in Geschool belonged to lower-level thinking skills, particularly remembering (cognitive dimension) of factual knowledge.Â Therefore, big efforts should be addressed to escape from such low level of knowledge.